Radical cyclopolymerization of a divinylbenzyl-p-tert-butylcalix[4]arene derivative - Costa, Alexandra I. (2020)
The synthesis and characterization of a new homopolymer (poly 1), obtained in the course of the radical polymerization of 25,27-bis-(4-vinyl-benzyloxy)-26,28-dihydroxy-p-tert-butylcalix[4]arene (1), is described. Homopolymerization of 1 in THF, using BPO or thermal initiation, afforded soluble polymers in good isolated yields (60–90%). Gel permeation chromatography (GPC) profiles showed unimodal distributions for all the analyzed polymers, which is indicative that chain branching reactions did not occur to a major extent. Molecular weights (Mn) ranging from 30,000 to 60,000 g mol−1 were reached within a 8 h period, when the reactions were conducted at 0.06–0.5 mol% of BPO or thermally initiated, showing relatively narrow polydispersity indexes (1.5–2.0). The structure of the polymers was deduced upon analysis of their 1H NMR and FT-IR spectra, which, in conjunction with GPC and solubility data led to their formulation as cyclopolymers.